Double-Bind on the Bench: Citizen Perceptions of Judge Gender and the Court. Issue 2 (8th June 2015) - Nelson, Kjersten
Abstract : Scholars of gender and politics have long discussed the various manifestations of the "double-bind" for women who seek political leadership. Using a survey experiment with a nationally representative sample, this article examines whether this double-bind exists for female judges. The study reveals that while gender stereotypes are not uniformly applied to female judges, women on the bench are assessed differently in terms of their empathy and knowledge under certain circumstances. The article then discusses the potential implications of these gendered assessments for perceptions of the court, its actions, and women who aspire to judicial roles.